Some blood parameters in cows of different ages - Ozdemir, H; Sezer, K; Kilic, S (Indian Veterinary Journal, 2005)
The purpose of the present study was to evaluate the presence of a correlation between age and some haematological and biochemical parameters in the dairy cows aged 5 years and above.